Consistent pattern of habitat and species selection by post-dispersal seed predators in a Mediterranean mosaic landscape (Plant Ecology, 2009)
There is still little information on effects of habitat degradation on post-dispersal seed predation at the landscape scale. The aim of this study was to determine the inﬂuence of habitat degradation and seed species on the variability of post-dispersal seedpredation rate. Experimental seed removal was investigated in six Mediterranean woody plant species, four trees (Pinus sylvestris, Quercus ilex, Acer opalus ssp. granatense, and Sorbus aria) and two shrubs (Berberis vulgaris and Crataegus monogyna), in an extensively used mosaic landscape on the Sierra Nevada massif (SE Spain). Seed depots were distributed over 2 years in ﬁve differently degraded landscape units, each one with three plots: shrubland; native forest; and dense, cleared and fenced reforestation stands. Predation was the highest in native forest, shrubland, and fenced reforestation, and the lowest in dense and cleared reforestation stands, being partially due to a positive correlation between shrub cover and post-dispersal seed predation. However, the main factors driving post-dispersal seed predation were intrinsic to seeds, as species preference explained most of the variance in our model for predation. The plant-species ranking was Quercus[ Pinus[Sorbus[Berberis[Acer[Crataegus, the dominant tree species being the most depredated. These ﬁndings are novel because they suggest for the ﬁrst time that species-selection patterns by postdispersal seed predators tended to remain constant through both study years in all habitats comprising a mosaic landscape, whether native forest, reforestation stands or successional shrubland.